TiO2 Nanocrystals and Annona crassiflora Polyphenols Used Alone or Mixed Impact Differently on Wound Repair - MOURA,FRANCYELLE B.R. DE (2022)
Abstract Wounds treated with TiO2 nanoparticles (TiO2-NPs) show an improvement in healing time. However, little is known about the parameters that can contribute to this result. On the other hand, the treatment of wounds with polyphenols is widely known. These compounds are found in the peel of Annona crassiflora fruit and have antioxidant, analgesic and anti-inflammatory properties. In this study, we evaluated the healing effect of TiO2 nanocrystals (TiO2-NCs), polyphenolic fractions obtained from ethanolic extract of A. crassiflora fruit peel (PFAC) and mix (PFAC + TiO2-NCs) on the parameters of wound closure, inflammation, collagen deposition, metalloproteinase activity (MMPs) and angiogenesis. TiO2-NCs and PFAC have activity for wound healing, showed anti-inflammatory action and a shorter wound closure time. These treatments also contributed to increased collagen deposition, while only treatment with TiO2-NCs increased MMP-2 activity, parameters essential for the migration of keratinocytes and for complete restoration of the injured tissue. The combination of PFAC + TiO2-NCs reduced the effectiveness of individual treatments by intensifying the inflammatory process, in addition to delaying wound closure. We conclude that the interaction between the hydroxyl groups of PFAC polyphenols with TiO2-NCs may have contributed to difference in the healing activity of skin wounds.